Peran Baitul Maal Wat Tamwil (BMT) dalam Mewujudkan Ekonomi Syariah yang Kompetitif - Krisna Sudjana; Rizkison Rizkison (ITB AAS INDONESIA Surakarta, 2020)
Sharia microfinance institution Baitul Maal Wat Tamwil (BMT) is perfect for tackling economic problems on the microeconomic base. BMT uses Sharia principles and is free of riba which is banned in Islam. The function of this institution is as a supporter of the enhancement of economic efforts of micro and small entrepreneurs based on sharia systems. The objective of BMT activities that have a close relationship with the Sharia economics business, first is target result, second is growth, third is sustainability, last is blessing. Entrepreneurs should keep the orientation of this blessing to be the vision of its business, so that always in business activities always be in control of the sharia and the scourge of Allah. These four points became the main principle of BMT in its realization in the field. The role of BMT in economic strengthening is the increased employment opportunities and the application of financial systems based on the outcome in realizing equality, honesty, and fairness. By implementing the principles of Sharia and the Islamic power into real life, the spiritual values are aimed at directing and mobilizing dynamic, proactive, progressive, fair and moral ethics.